2017
DOI: 10.18632/oncotarget.23684
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the MEK/ERK pathway augments nab-paclitaxel-based chemotherapy effects in preclinical models of pancreatic cancer

Abstract: Nab-paclitaxel (NPT) combination with gemcitabine (Gem) represents the standard chemotherapy for pancreatic ductal adenocarcinoma (PDAC). Genetic alterations of the RAS/RAF/MEK/ERK (MAPK) signaling pathway yielding constitutive activation of the ERK cascade have been implicated as drivers of PDAC. Inhibition of downstream targets in the RAS-MAPK cascade such as MEK remains a promising therapeutic strategy. The efficacy of trametinib (Tra), a small molecule inhibitor of MEK1/2 kinase activity, in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…MEK-1 activity through its phosphorylation has been confirmed [28][29][30]. In the present study, we highlight the roles of ALDH1 in the regulation of MEK-1 mRNA stability and translation.…”
Section: Discussionsupporting
confidence: 57%
“…MEK-1 activity through its phosphorylation has been confirmed [28][29][30]. In the present study, we highlight the roles of ALDH1 in the regulation of MEK-1 mRNA stability and translation.…”
Section: Discussionsupporting
confidence: 57%
“…Several kinds of strategy have been carried out to reverse Dox resistance in breast cancer according to its corresponding mechanism, including developing chemosensitizers, improving drug delivery systems, modulating drug resistance‐related signaling pathways, and etc. Among these strategies, chemosensitizers are the earliest and most studied; however, most of the chemosensitizers either necessitate higher doses or increase their blood drug concentration while increasing the chemotherapeutic drugs concentration in tumor cells, thereby causing serious toxic side effects (Bates et al, ; Ozols et al, ); therefore, they cannot be widely used in clinic; though improving drug delivery systems can increase chemotherapeutic drugs concentration in tumor cells (Chen et al, ; Zhong et al, ), it cannot be widely used in clinic because it cannot reduce the toxic side effects caused by high concentration of chemotherapeutic drugs; though regulating drug resistance‐related signaling pathways can reverse tumor cells resistance (Awasthi, Monahan, Stefaniak, Schwarz, & Schwarz, ; Yang et al, ), it also can cause the dysfunction of the corresponding signaling pathway in normal cells; therefore, regulating drug resistance‐related signaling pathways to reverse tumor cells resistance also cannot widely be used in clinic. Though Dox is the first‐line drug for breast cancer chemotherapy, it is currently usually used in combination with one or two chemotherapeutic drugs, which may achieve better therapeutic effects while accumulating the toxic side effects of other chemotherapeutic drugs, thereby may affect the life quality of breast cancer patients and even limit the clinical application of chemotherapy (Veronese et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that specific molecules can affect the tumorigenesis, progression, incursion as well as migration of pancreatic cancer by participating in the regulation of JAK/STAT pathway . MAPKKK cascade is the key molecule in the MAPK pathway, and MAPK pathway can be incorporated to control cell propagation, invasion, migration, apoptosis, tumorigenesis, and progression of pancreatic tumor, as well as chemotherapy response and clinical outcomes . For the two drugs that were identified in our current study, no previous studies have identified their functions on cancer treatment.…”
Section: Discussionmentioning
confidence: 88%
“…[41][42][43][44] MAPKKK cascade is the key molecule in the MAPK pathway, and MAPK pathway can be incorporated to control cell propagation, invasion, migration, apoptosis, tumorigenesis, and progression of pancreatic tumor, as well as chemotherapy response and clinical outcomes. [45][46][47][48][49][50][51] For the two drugs that were identified in our current study, no previous studies have identified their functions on cancer treatment. These two drugs as the targeted agents for pancreatic cancer remain to be confirmed by further research as well as clinical trials.…”
Section: Discussionmentioning
confidence: 96%